On poundings of a seismically isolated building with adjacent structures during strong earthquakes. - Polycarpou, Panayiotis C.
This paper presents selected indicative results from an extensive parametric investigation that has been performed in order to assess the effects of potential earthquake-induced poundings on the overall dynamic response of seismically isolated buildings. In particular, a seismically isolated building and its adjacent fixed-supported buildings are subjected to various earthquake excitations that induce structural impact among the buildings in series. The results indicate that the seismically isolated building may hit against the adjacent buildings at the upper floor levels before the occurrence of any pounding at the isolation level with the surrounding moat wall. The severity of the impact depends on the dynamic properties of the adjacent buildings, in combination with the earthquake characteristics.
Keywords: Poundings; Seismic isolation; Impact; Adjacent buildings; Seismic gap